Hubungan promosi kerja dan kondisi kerja dengan kinerja perawat di ruang rawat inap Rumah Sakit Umum Wulan Windy - Ramadhani, Safrina; Situmorang, Rupina Kanasia; Hsb, Sindy Syaputri (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Work motivation is a state or situation that cause a person to continue to improve, direct, and sustain his behaviour both directly and indirectly with his work environment.This study aimed to determined the relationship of job promotion and working condition to nurse performance.This is quantitative research with a cross sectional approach, the population was 103 nurses in inpatient room and the sample was 51 nurse data collection techniques used questionnaires. The result showed that the variable of job promotion acquired (0.035) had a link with nursing performance. While the working condition (0,256). The conclusion job promotion have a relationship with nurse performance, whereas working condition have no relationship with nurse performance.